1995
DOI: 10.1159/000462905
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Flow Cytometric Determination of HLA Class I Antigens, 'Platelet-Specific' Glycoproteins and Activation Markers

Abstract: Flow cytometry (FC) provides a reproducible investigation of cell surface antigens on platelets. The aim of this study was to elaborate appropriate protocols and to compare them with other techniques that have already been published. (1) Venipuncture with tubes containing citrate was better for the preservation of the antigenicity than using ACD tubes. The isolated platelets could not be completely distinguished from detritus and protein aggregates. Therefore a platelet concentration between 10^7 and 10^8/ml m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This receptor is highly upregulated in activated PLT. The demonstration of PLT in diluted whole blood using a rejec tion gate to screen out RBC and WBC is quick and accurate [13], A similar method using the MAB CD41 and CD42b was described by Dickerhoff and von Ruecker [14]. In dilu tion experiments, these authors found good linearity of FC measurements up to a DL of 50 xlO9 PLT/1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This receptor is highly upregulated in activated PLT. The demonstration of PLT in diluted whole blood using a rejec tion gate to screen out RBC and WBC is quick and accurate [13], A similar method using the MAB CD41 and CD42b was described by Dickerhoff and von Ruecker [14]. In dilu tion experiments, these authors found good linearity of FC measurements up to a DL of 50 xlO9 PLT/1.…”
Section: Discussionmentioning
confidence: 99%
“…Since impedance-based cy tometers for PLT counting fail at low PLT concentrations and counting with a microscopic chamber is unreliable be cause of the small size of PLT, the whole-blood method is the most reliable one available today. However, it can pro vide inaccurate measurements if the PLT are significantly activated in vitro or in vivo [13]. In this case, the activated PLT partially aggregate, are located in the area of the rejec tion gate set in the scatter dot plot and are excluded from the measurement.…”
Section: Discussionmentioning
confidence: 99%